Gastric Volvulus - A Rare Entity - Atta Ur Rehman; Mobeen Ikram; Abdul Rauf (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Gastric volvulus is seldom seen in clinical practice. The clinical triad, of upper abdominal pain, intractable retching and inability to pass nasogastric (NG) tube, if found, can help in diagnosis. It can lead to gangrene and perforation of the stomach if remained undiagnosed or treated late. Both acute and chronic presentation is seen. The chronic form is more common than acute clinical presentation but the latter is associated with more complications. Laxity of gastric ligaments, made up of peritoneal folds is responsible for this condition. The knowledge of the condition, timely diagnosis and early surgical management is essential for a favourable outcome as done in the case being presented.